Neophilia dan Dampaknya Bagi Kualitas Pengalaman Penikmat Makanan Lokal Kota Kebumen - Wibawanto, Sigit (P4M STIE Putra Bangsa, 2020)
This study is limited to the discussion of food consumption which is explored from the dimensions of local food preferences in destinations. This study has three objectives: to establish the neophilic tendency of foods to determine the consumption of new foods; how is the quality of food experiences with neophilia personalities; and how tourist food experiences are moderated by travel motives for new experiences about food in the places visited. This study illustrates a descriptive research scheme, tested on travelers who happen to pass through the city of Kebumen who enjoy